2005
DOI: 10.1253/circj.69.507
|View full text |Cite
|
Sign up to set email alerts
|

'Gadolinium' as an Alternative to Iodinated Contrast Media for X-Ray Angiography in Patients With Severe Allergy

Abstract: -ray coronary angiography (CAG) is an indispensable examination technique for the diagnosis of coronary artery disease and for determination of therapeutic strategies. However, an anaphylactic reaction to the iodinated contrast media can be life-threatening. Gadolinium-based contrast media have been developed to improve the quality of magnetic resonance imaging (MRI) and are considered to be safer and less nephrotoxic than the iodinated agents. It has been recently reported that computed tomography (CT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…As such, renal failure is a relative contraindication, as well as pregnancy and breastfeeding. [7][8][9][10] ] Generally, for tumors to grow more than 2 to 3 mm in size, they have to secrete proangiogenic factors. Higher grade tumors are usually associated with increased vascularity.…”
Section: 3mentioning
confidence: 99%
“…As such, renal failure is a relative contraindication, as well as pregnancy and breastfeeding. [7][8][9][10] ] Generally, for tumors to grow more than 2 to 3 mm in size, they have to secrete proangiogenic factors. Higher grade tumors are usually associated with increased vascularity.…”
Section: 3mentioning
confidence: 99%
“…20,21 The use of alternatives to iodinated contrast is another approach to preventing CIN. 8 It has been reported that CAG or PCI can be done with a gadolinium contrast agent; 22,23 this appears to be a feasible alternative method for patients with CRI.…”
Section: Other Methods To Prevent Cinmentioning
confidence: 99%
“…When used in recommended doses, Gd has been shown to be safe, well-tolerated, and not nephro-toxic [31][32][33][34]. However, Gdbased agents have been associated with suboptimal but acceptable quality in angiography [31,32,35,36]. Specifically for cardiac procedures, Gd has rarely been used due to suboptimal image quality.…”
Section: X-ray Attenuationmentioning
confidence: 99%
“…Specifically for cardiac procedures, Gd has rarely been used due to suboptimal image quality. Although some operators report low adverse event rates [36][37][38][39], others have reported the occurrence of significant ventricular arrhythmias during coronary angiography [40]. Although lacking the more definitive evidence-based on large-scale randomized controlled trials, current literature shows that Gd can be an alternative agent in selected patients with severe allergic reaction to iodine contrast.…”
Section: X-ray Attenuationmentioning
confidence: 99%
See 1 more Smart Citation